Vernacularisation of Sufism in the Balkans: The Example of the ‘Shpija e Zotit’ (House of God) Treatise - Xhafçe, Zeqije; Rexhepi, Abdulla (Ulumuna, 2024)
Sufism, beyond being a philosophical discipline, is a way of life to enhance individual and societal existence. The concrete product of the intellectual and spiritual effort shown in Sufism has often emerged in poetry or prose. This study examines a Sufi manuscript as a form of Sufi legacy that significantly influenced the Muslim Albanian community in Ottoman territories. The focus is on the treatise "House of God," featuring prose texts by ʿAbd al-Mālik Ḥilmī, included in his collection of Sufi treatises known as ‘Risalet’. The study explores the general characteristics of Sufi texts, particularly those preserved in Kosovo's tekkes. Through field research, interviews, and literature review, data on ʿAbd al-Mālik Ḥilmī 's life and works were compiled. It was found that manuscript works of some authors remain under-researched. The treatise is analyzed linguistically, highlighting the author's didactic style and word choices. Sufi terms used in the text were extracted and classified according to their usage in contemporary Albanian standards. The author's efforts toward the vernacularization of Sufi terms demonstrate his belief in conveying Sufi thought in the local language. Based on references in the anthology text, assumptions about ʿAbd al-Mālik Ḥilmī 's Sufi thought are presented. Sample passages from Hilmi's work in Albanian are translated into English.